Adolf Piquer & Adéla Koťátková (ed.), «Character and Gender in Contemporary Catalan Literature», Berlín, Peter Lang Verlag, 2022, 222 p. - Cuesta Esteve, Teresa (Caplletra. Revista Internacional de Filologia, 2024)
Ressenya sobre el llibre d'Adolf Piquer & Adéla Kotátková (ed.), Character and Gender in Contemporary Catalan Literature, Berlín, Peter Lang Verlag, 2022, 222 p., ISBN: 9783631880616.